2015
DOI: 10.18869/acadpub.ijal.18.2.165
|View full text |Cite
|
Sign up to set email alerts
|

External Factors Affecting Second Language Motivation: The Role of Teacher Burnout and Family Influence

Abstract: Motivation can be conceptualized as a dynamic process which is a key contributor to mastering a second language. This study used the L2-Motivational Self System as the basis for a conceptual framework for studying the effects of external factors on learners' motivation. In particular, the role of teachers and parents was studied as the external facets of predicting learners' motivation. One hundred and twenty EFL teachers along with 1,270 of their students participated in the study. To measure motivation, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
3
6
1
Order By: Relevance
“…Academic resilience is indeed the emotional affective consequence of goal orientations. It is indicated that students are more successful if they adopt a mastery orientation or intrinsic motivation (Fortune, Sinclair & Hawton, 2008;Rostami, Ghanizadeh, & Ghonsooly, 2015). The results of the present study are in harmony with a study conducted by Splan, Brooks, Porr & Broyler (2011) among university students.…”
Section: Discussionsupporting
confidence: 89%
“…Academic resilience is indeed the emotional affective consequence of goal orientations. It is indicated that students are more successful if they adopt a mastery orientation or intrinsic motivation (Fortune, Sinclair & Hawton, 2008;Rostami, Ghanizadeh, & Ghonsooly, 2015). The results of the present study are in harmony with a study conducted by Splan, Brooks, Porr & Broyler (2011) among university students.…”
Section: Discussionsupporting
confidence: 89%
“…More recently, Rostami, Ghanizadeh, and Ghonsooly (2015), conducted a study to examine the role of teacher burnout and family influence as two external factors in student motivation. In particular, four factors were considered in this study: (a) criterion measures which examine student intended efforts towards learning the language, (b) instrumentality-promotion that measures the regulation of personal goals, (c) attitudes to learning which assess situation-specific motives, and (d) family influence which examines parental roles regarding learning the language.…”
Section: International Journal Ofmentioning
confidence: 99%
“…In the study done by Rostami et al (2015), the external factors that affect second language learning motivation were investigated. In their study, 120 efl teachers along with 1,270 of their students participated and Dornyei's l2 Motivation Self-System Scale for students and the educator version of the Maslach Burnout Inventory (mbies) were used for data collection purposes.…”
Section: Teachers' Burnoutmentioning
confidence: 99%